MENGOPTIMALKAN TASK BASED TEACHING AND LEARNING - admin, admin; Anwar, Khoirul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2017)
Some researches reveal that skill courses and content courses so far, especially in the area of English learning, have pointed out shortcomings and weaknesses so that the activities of learning English in the classroom are often not optimal. This article aims to provide an offer of how to optimize a method of learning English using the task based learning. This article also offers the essence of the task that should be developed to maximize the learning atmosphere in the classroom so that the achievement and attainment of learning can be maximized as well.